The Four-Herb Chinese Medicine Formula Tuo-Li-Xiao-Du-San Accelerates Cutaneous Wound Healing in Streptozotocin-Induced Diabetic Rats through Reducing Inflammation and Increasing Angiogenesis - Xiao-na Zhang; Ze-jun Ma; Ying Wang; Yu-zhu Li; Bei Sun; Xin Guo; Cong-qing Pan; Li-ming Chen (Journal of Diabetes Research)
Impaired wound healing in diabetic patients is a serious complication that often leads to amputation or even death with limited effective treatments. Tuo-Li-Xiao-Du-San (TLXDS), a traditional Chinese medicine formula for refractory wounds, has been prescribed for nearly 400 years in China and shows good efficacy in promoting healing. In this study, we explored the effect of TLXDS on healing of diabetic wounds and investigated underlying mechanisms. Four weeks after intravenous injection of streptozotocin, two full-thickness excisional wounds were created with a 10 mm diameter sterile biopsy punch on the back of rats. The ethanol extract of TLXDS was given once daily by oral gavage. Wound area, histological change, inflammation, angiogenesis, and collagen synthesis were evaluated. TLXDS treatment significantly accelerated healing of diabetic rats and improved the healing quality. These effects were associated with reduced neutrophil infiltration and macrophage accumulation, enhanced angiogenesis, and increased collagen deposition. This study shows that TLXDS improves diabetes-impaired wound healing.